Application web pour la gestion des matchs - HARIZ BEKKAR, Mohammed; BEN NACER, Riad; GUERFI, Afīf (university of eloued جامعة الوادي, 2018)
ھذا العمل جزء من تطویر تطبیق ویب لإدارة المباریات. إن أھمیة ھذا العمل في مثل ھذه العملیة یصعب تحقیقھا یدویاً في ضوء العدد الكبیر من النوادي والحكام . لذلك حاولنا من خلال ھذا التقریر أن نعطي فكرة عن الخطوات وكیفیة إنشاء UML ھذا مولد تلقائي، وذلك من خلال رسوم وفقرات توضیحیة ومخططات في خطوات منتظمة تحاكي خطوات عملنا في عملیة التحضیر والبرمجة. واستطعنا بعد كل ھذا أن ننتج تطبیقا یقوم بالمھمة المطلوبة، والذي أدرجنا صورا عنھ في نھایة التقریر.This work is part of the development of a web application for the management of matches. The importance of this work in the process like this is difficult to accomplish manually in light of the large number of clubs, referees, so we have tried through this report is to give an idea of the steps and how to create this automatic generator, through taxes and paragraphs illustrative diagrams UML in the regular steps emulate the steps of our work in the process of preparation and programming. And after all that, we were able to produce the necessary
licence mémoire informatique